Mobilizing the resources - the flow of savings - Popkin, John W.; Macdonald, William A.; Canadian Economic Policy Committee ([Montreal : Private Planning Association of Canada, 1971)
The flow of savings and its investment as a crucial perspective for achieving tax reform in Canada
Commissioned by the Canadian Economic Policy Committee.
obn22/01/2019
Loans
Keywords: Saving and investment; Taxation